Durability design of concrete structures in severe environments - Gjorv, Odd E. (CRC Press/Taylor & Francis, 2014)
Preface Concrete structures in severe environments include a variety of structures in various types of environment. Therefore, improved procedures for quality control and quality assurance during concrete construction are also very important.